Smoking as a major risk factor for cervical cancer and pre-cancer: Results from the EPIC cohort - Roura, E; Castellsagué, X; Pawlita, M; Travier, N; Waterboer, T; Margall, N; Bosch, F; De Sanjosé, S; Dillner, J; Gram, I; Tjønneland, A; Munk, C; et al. (Wiley-Liss Inc., 2014)
A total of 308,036 women were selected from the European Prospective Investigation into Cancer and Nutrition (EPIC) study to evaluate the association between tobacco smoking and the risk of cervical intraepithelial neoplasia of grade 3 (CIN3)/carcinoma in situ (CIS) and invasive cervical cancer (ICC). At baseline, participants completed a questionnaire and provided blood samples. During a mean follow-up time of 9 years, 261 ICC cases and 804 CIN3/CIS cases were reported. In a nested case-control study, the baseline sera from 609 cases and 1,218 matched controls were tested for L1 antibodies against HPV types 11, 16, 18, 31, 33, 35, 45, 52, 58, and antibodies against Chlamydia trachomatis (CT), and Human Herpes Virus 2 (HHV-2). Cervical samples were not available for HPV-DNA analysis in this study. Multivariate analyses were used to estimate associations between smoking and risk of CIN3/CIS and ICC in the cohort and the case-control studies. In the cohort analyses smoking status, duration and intensity showed a two-fold increased risk of CIN3/CIS and ICC, while time since quitting was associated with a two-fold reduced risk. In the nested case-control study, consistent associations were observed after adjustment for HPV, CT and HHV-2 serostatus, in both HPV seronegative and seropositive women. Results from this large prospective study confirm the role of tobacco smoking as an important risk factor for both CIN3/CIS and ICC, even after taking into account HPV exposure as determined by HPV serology. The strong beneficial effect of quitting smoking is an important finding that will further support public health policies for smoking cessation. What's new? Tobacco smoking is a cited cause of cervical cancer, but whether it causes cervical malignancy independent of human papillomavirus (HPV) infection is unclear. Here, strong associations were found between most measures of tobacco smoking and the risk of cervical intraepithelial neoplasia of grade 3/carcinoma in situ and invasive cervical cancer, after taking into account past exposure to HPV infection. Quitting smoking was associated with a 2-fold risk reduction. The findings confirm the role of tobacco smoking in cervical carcinogenesis and show that quitting the habit has important benefits for cancer protection. © 2013 UICC.